A review on piezoelectric material as a source of generating electricity and its possibility to fabricate devices for daily uses of army personnel. (2015) - Mishra, Ritendra; Jain, Shruti; Prasad, C. Durga
Energy harvesting, a process of capturing ambient waste energy and converting it into usable electricity, has been attracting more and more researchers' interest because of the limitations of traditional power sources. In this study, fabrication of flexible piezo composite material was investigated using lead zirconate titanate (PZT) powder (3 µ and 1 µ particle size), multiwalled carbon nano tubes (MWCNT) (diameter 5-20 nm, length up to 10 µ), polydimethyl siloxane (PDMS) synthetic silicone rubber and solvents THF, chloroform. These materials have been tested for their peak performance, lifetime and durability under different conditions. The foremost aim will be to extract usable power which can run various devices having low power requirement such as mobile devices and wireless sensor networks and the recent advent of the extremely low power electrical and mechanical devices such as micro electromechanical systems (MEMS).